THE VOYAGE OF THE DAWN TREADER : THE CHRONICLES OF NARNIA - LEWIS, C.S.; C.S. LEWIS (New York HarperCollinsPublishers, 1994)
"Welcome aboard the royal vessel of King Caspian! Meet our captain, Lord Drinian; Sir Repicheep, the bravest of all mice; Edmund and Lucy Pevensie; and others as they search for the seven lost lords of Narnia"
English
Keywords: Fantasy; Fantasy fiction